Effect of graphene nanoreinforcement on moisture absorption and mechanical properties of epoxy adhesive joint - Nurziana, Kong (2023)
Adhesive can be used to join various types of substrates and is used in various industries. However, there is a problem with exposure to moisture/humidity. Some adhesives tend to absorb moisture in humid environments, leading to a decrease in joint strength. Addition of nanoparticles into polymer adhesive is expected to reduce water uptake by increasing the water resistance against moisture attack, subsequently, maintain the joint strength, and it has been studied numerous times previously. However, some studies showed an opposing manner to the improvement. Therefore, in the current work, the effects of Graphene Nanoplatelets (GNP) reinforcement on the moisture absorption behaviour, mechanical properties of ASTM E8 specimens and single lap joints with epoxy adhesive were investigated. Epoxy adhesive with different GNP contents (0.0, 0.5, 1.0, 1.5, and 2.0 wt%) was used to join aluminium adherends that were subjected to different immersion periods (0, 10, 20, 30, 40, 50, and 60 days). Then, the effect of GNP reinforcement on water uptake, water absorption rate, tensile and shear properties, and fracture mode of the joint specimens was investigated. As compared to the pristine adhesive, moisture specimens at lower GNP content (i.e.,0.5 and 1.0 wt%), the reinforcement resulted in an increase of water uptake and water absorption rate up to 99.77% at early immersion stage, while, resulted in a decrease up to 18.37% for longer immersion period. At higher GNP content (i.e., 1.5 and 2.0 wt%), higher water uptake and water absorption rate up to 124.63% were recorded at lower immersion periods (i.e., 10-20 days), whereas lower water uptake and water absorption rate up to 51.50% were observed at higher immersion period (i.e., 30-60 days). The tensile properties of the ASTM E8 specimens demonstrated an enhancement in the ductility of the specimens by up to 933.43% for 1.0 wt% when compared to pristine adhesive. At the same time, reduction in tensile stress up to 74.35% was observed for 1.5 wt%. The correlation coefficient R showed an improvement in ductility of ASTM E8 specimens as water uptake increased for all GNP contents, with a higher R value observed for 1.0 and 1.5 wt%. Simultaneously, tensile stress decreased with increasing water uptake for all GNP contents, with the lowest R value observed at 1.0 wt%. The Field Emission Scanning Electron Microscope revealed that there were some possible toughening mechanisms and some GNP agglomerations which affect the failure behaviour of the specimens. The shear properties of single lap joints generally showed a decrease in shear stress performance up to 64.84% at 2.0 wt% when the immersion period was increased. Fracture elongation demonstrated reduction in ductility up to 45.98% at 1.5 wt%. Incorporation of GNP into the epoxy matrix resulted in a mixed mode fracture behaviour. The increment of cohesive fracture (CF) corresponded to the lower shear stress performance (or cohesive strength) and the lower fracture elongation of the specimens, while the increment of adhesive fracture (AF) corresponded to the higher shear stress performance (or cohesive strength) and the higher fracture elongation of the specimens. In brief, the addition of GNP into epoxy adhesive increased the water uptake and water absorption rate at early immersion period, while, reducing them at a longer immersion period. Meanwhile, the GNP addition improved the ductility of the ASTM E8 specimens, but weakened the properties of the adhesive matrix, causing failure of the single lap joints occurred at lower forces and lower ductility. These specimens exhibited mixed mode fracture behavior. Higher CF region corresponded to lower cohesive strength. Based on the ASTM E8 specimens, it was found that the tensile strength, which corresponded least with water uptake, associated with the largest fracture elongation is at 1.0 wt% GNP content.